A conceptual model of connection of strategies and operations in organisations: a perspective of management control. (22nd January 2010) - Lin, Hua; Zhang, Runtong; Andersson, Birger
This paper proposes a conceptual framework of management control systems in the informational perspective, in order to connect strategies and operations. The framework takes strategic planning and control as a whole, and integrates diagnostic control and interactive control into the same framework. It conceptualises the related functions to five components, and shows their interactions and work flows. Formulation and implementation of strategies or strategic change are explained under this framework, focusing on the roles of diagnostic control and interactive control. We use enterprise modelling techniques, i* and e³ value, to describe goal model, business model and their alignment. The connection model is to improve organisational effectiveness and efficiency, by discovering and correcting deviations and taking opportunities. To illustrate and validate the model, a case study is done, showing how the framework works for bridging strategies and operations and how strategic change could be triggered and implemented under the framework.